THE BIBLICAL VIEW OF DIOGENES' CYNICISM PHILOSOPHY IN CHRISTIANITY - Harold Siregar; Bartolomeus Diaz Nainggolan (Bethel Press, 2024)
This study aims to find out whether the Bible supports those who are cynical, especially the cynicism of Diogenes. This type of research is useful to examine a topic that has not been studied in depth before or to broaden one's understanding of a topic that has been studied before using various perspectives. This research collects and studies all literature and sources related to the Philosophy of Cynicism, especially Christian spiritual literature sources such as the Bible. Lack of faith, or